Kin recognition in Drosophila: rearing environment and relatedness can modulate gut microbiota and cuticular hydrocarbon odour profiles - García‐Roa, Roberto; Domínguez‐Santos, Rebeca; Pérez‐Brocal, Vicente; Moya, Andrés; Latorre, Amparo; Carazo, Pau (Oikos, 2022)
From inbreeding avoidance to kin‐selected cooperation, social behaviours are frequently reliant on kin recognition. However, kin recognition mechanisms are costly to evolve and currently not very well understood. Recent evidence suggests that, by altering their host's odour, gut and other host‐associated microorganisms may provide a promising avenue for understanding kin recognition. In Drosophila melanogaster, kin recognition can mediate mate choice, sexual conflict and larval competition/cooperation, underscoring its important functional role. As is commonly the case, kin recognition in this species depends on both familiarity (i.e. shared rearing environment) and relatedness, and seems to rely mainly on body odours determined by cuticular hydrocarbons. Here, we investigated the degree to which larval rearing environment and relatedness (full‐sibs versus unrelated) determine co‐variation between gut microbiota and cuticular hydrocarbons in D. melanogaster. We found that rearing environment strongly determined microbiota composition and cuticular hydrocarbon profiles, but that these effects were independent from each other. In contrast, relatedness did not influence microbiota composition, but had a strong influence on microbiota diversity, which in turn covaried significantly with cuticular hydrocarbon profiles. Our results show that, in D. melanogaster, odours may convey information about both familiarity and relatedness via an interaction between: 1) direct effects of the rearing environment on cuticular hydrocarbons and 2) indirect effects of relatedness on cuticular hydrocarbons via gut microbiota diversity.